Analisis Perbandingan Tingkat Kesejahteraan Peternak dengan Petani Tanaman Pangan, Hortikultura, Perkebunan dan Perikanan di Provinsi Sumatera Utara - Theofhani Cicionta Br Ginting; Afriani H; Firmansyah Firmansyah; Farizal Farizal; Fachroerrozi Hoesni (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to analyze the level of welfare of livestock farmers in North Sumatra Province and compare it with the welfare of food crop, horticulture, plantation, and fishery farmers based on the Farmer Exchange Rate (NTP) indicator during the 2008–2024 period. The study used a quantitative method with a descriptive analytical approach, utilizing secondary data obtained from the official publication of the Central Statistics Agency (BPS) of North Sumatra Province. Data analysis was carried out by calculating the price index received by farmers (It), the price index paid by farmers (Ib), and the NTP as the main indicator of welfare. To test differences between subsectors, the Kruskal-Wallis test and the Mann–Whitney test were used. The results showed that in general, the NTP of farmers in North Sumatra Province fluctuated throughout the study period. The plantation subsector had the highest NTP with an average of 115.29, followed by the livestock subsector (104.51), fisheries (101.24), food crops (97.31), and horticulture (93.99). This shows that plantation sub-sector farmers have the highest level of welfare, while food crop and horticultural farmers are still below the welfare standard (NTP < 100).